Advanced quantum chemical and electrochemical analysis of ravage drugs for corrosion inhibition of mild steel. Issue 10 (19th May 2019) - Dahiya, Shefali; Pahuja, Priti; Lgaz, Hassane; Chung, Ill-Min; Lata, Suman
Abstract: The blocking of corrosive sites of soft (mild) steel has been studied using ravage drugs Pyrazinamide (Z), Isoniazid (H) and Rifampicin (R) in 0.5 M HCl medium. The degree of ability of these drugs to act as corrosion controlling agents was investigated by gravimetric measurements, potentiostatic polarization and electrochemical impedance spectroscopy. Their inhibition efficacy has, further been validated through theoretical and simulation studies. Though, all the drugs have shown good anticorrosive impact, but, rifampicin (R) has proven its greater efficacy as 97.06% at 1000 ppm and at 303 K. Polarization curves depict that the H and R drugs act through mixed mode of inhibition while Z drug is predominantly anodic in nature. The result of electrochemical impedance spectroscopy specifies that the corrosion reaction is resisted by charge transfer process. Morphology of un-corroded and corroded coupons was studied by scanning electron microscopy. The mechanism of adsorption is obeyed well through Langmuir isotherm and advocated a significant physiochemical type of interaction by the compounds on the metal surface. Thus, all the findings got via various experimental techniques along with that of obtained using Molecular Dynamics (MD) and Density Functional Theory (DFT) for the three compounds are in proper harmony.